Democratization of Islamic Education Through School-Based Management - Ridho, Ali; Zainollah, Zainollah; Ismail, Ismail; Primarni, Amie (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2021)
This research raises democratization of Islamic education through application of Islamic Education Institution Management, SBM as a tool for educational institution to realize democratic Islamic education. Law No. 20 of 2003 concerning National Education System and quality assurance through 2005 Law on National Education Standard which all demonstrate the democratization of education. This study uses a qualitative approach by describing application of School-Based Management in Islamic educational institution, and analyzing that application of School-Based Management is a way of realizing democratic Madrasah. The results of the study showed that the reference of implementation of SBM in Madrasah starts from Law no. 2 of 1989, No. 20 of 2003, PP No. 19 of 2005 and PP No. 55 of 2007. The strategy of SBM implementation is autonomy, empowerment, independence and flexibility. While the stages of its implementation are by way of socialization, formulation of vision and mission goals, identification of challenges, identification of functions, SWOT analysis, alternative solutions, quality improvement plan, implementation of quality improvement, and evaluation and monitoring. Implementation of School-Based Management strongly shows the existence of democratization in education, this is reflected in principles of a democratic form of Islamic education including respect for the potential of Madrasah, dynamic curriculum and the creation of synchronization of educational institutions with community as customer.